Family firms' sustainable longevity: the role of family involvement in business and innovation capability - Ahmad, S. (Emerald Group Holdings Ltd., 2021)
Purpose: The objective of this research is to investigate the influence of family involvement in business and innovation capability on sustainable longevity of family firms. Design/methodology/approach: Data collected from 553 executives of 200 family firms that survived to the second generation and beyond was analyzed using partial least square (PLS) approach of structural equation modeling (SEM) to test the hypotheses and validate the model. Findings: The results provided evidence of the significant influence of family involvement in business on sustainable longevity of family firms and partial mediation of innovation capability between family involvement in business and corporate sustainable longevity. Research limitations/implications: The sample included family firms owned and governed by the owner family. The future researchers may focus on professionally managed or publicly listed family firms. Practical implications: The path to family firms' sustainable longevity goes through innovation capability apart from effective family control, succession, commitment to the business and family enrichment. That requires the family firm to be proactive in innovation capability. Originality/value: Family firms are the dominant form of business representing around 80% of global business structure that strives for survival and consistently pursues sustainable longevity strategies. In the current globally competitive environment, innovation capability has become a matter of life and death for any firm. Based on the transaction cost economics (TCE) theory of family firms, this study proposes an integrative model of sustainable longevity for family firms.